2019
DOI: 10.1007/s10592-019-01162-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity of two bioeconomically important kelp species along the Norwegian coast

Abstract: 25Knowledge of genetic diversity among wild populations is becoming increasingly important as more species are 26 recognized for their bioeconomic value. Industrialization of natural resources, such as kelp in the marine 27 shallow sublittoral zone through cultivation and wild-harvesting, may lead to extensive translocation and local 28 population decimation. Without adequate resilience in the form of genetic diversity within and across 29 populations and given the potential introduction of deleterious alleles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 94 publications
6
18
5
Order By: Relevance
“…A pattern of increasing genetic diversity with increasing latitude had previously been observed for European S. latissima at several spatial scales [29,33], a pattern opposite to that expected under the hypothesis of latitudinal cline of genetic variability, though ours is the first study to investigate the hypothesis of a latitudinal cline of genetic variability across the entire eastern Atlantic range of this kelp species. There are several potential non-mutually exclusive reasons, including both historical and contemporary causes, that may explain the reported patterns of S. latissima genetic diversity.…”
Section: No Decrease In Within-population Genetic Diversity With Laticontrasting
confidence: 94%
See 2 more Smart Citations
“…A pattern of increasing genetic diversity with increasing latitude had previously been observed for European S. latissima at several spatial scales [29,33], a pattern opposite to that expected under the hypothesis of latitudinal cline of genetic variability, though ours is the first study to investigate the hypothesis of a latitudinal cline of genetic variability across the entire eastern Atlantic range of this kelp species. There are several potential non-mutually exclusive reasons, including both historical and contemporary causes, that may explain the reported patterns of S. latissima genetic diversity.…”
Section: No Decrease In Within-population Genetic Diversity With Laticontrasting
confidence: 94%
“…Overall, the strong genetic structuring that we report here for S. latissima is in agreement with previous analyses of the population structure in this kelp species [29,33,70]. However, compared with the previous published studies, the high discriminant power of SNP markers developed as part of this study suggests that these markers could prove very useful for kelp aquaculture to detect individual migrants (or genetic pollution) between S. latissima populations when separated by at least 300 km.…”
Section: Low Connectivity Levels Between Disjunct S Latissima Samplisupporting
confidence: 92%
See 1 more Smart Citation
“…Breeding samples across these two regions is currently prohibited due to conservation concerns. Nonetheless, similar to other studies (Evankow et al, 2019), our recommendation supports the precautionary principle to only use regional ecotypes for cultivation, and to not interbreed kelp strains separated by Cape Cod. We also reveal a novel SNP association with a morphological trait and additional polymorphisms that may have been subject to selection in sugar kelp.…”
Section: Genetic Diversity In the Northeastern United Statessupporting
confidence: 88%
“…Recently, a number of population genetic analyses using molecular marker data have been conducted in order to describe the geographical pattern of genetic variation in kelp species. For example, based on microsatellite data, it has been shown that there is statistically significant genetic differentiation among both European and North-American populations of S. latissima, at least at distances above around 100 km (Guzinski et al, 2016;Nielsen et al, 2016;Paulino et al, 2016;Breton et al, 2018;Evankow et al, 2018;Luttikhuizen et al, 2018;Mooney et al, 2018). In spite of the genetic differentiation between populations, analysis of molecular variance indicated that most of the genetic variation (>90%) was found within populations rather than between populations (Breton et al, 2018;Mooney et al, 2018).…”
Section: Invasiveness Introduction Of Non-native Genotypes and Gene mentioning
confidence: 99%